2019
DOI: 10.3390/su11092574
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of an Energy Refurbishment Scheme on Adequate Warmth in Low-income Dwellings

Abstract: Many fuel poverty support programs have been implemented in the world. Energy-efficient retrofitting in low-income households is a main aspect of support programs in the context of energy saving, reduction of greenhouse gas emissions, and improvement of the thermal comfort and health of residents. This study analyzed the effects of an energy efficiency program for fuel poverty in Korea on the thermal comfort of residents. A total of 330 households were investigated wherein energy retrofits had been conducted. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Furthermore, the Korean government formalized an Energy and Welfare Statement; the Energy Act was legislated in 2006, and the government has operated the residential energy efficiency (retrofit) program for low-income households. The aims of this program are to improve the thermal performance and airtightness of households in fuel poverty, as well as to reduce heat loss, lower energy bills, and improve the thermal comfort and health problems of residents [15]. This program involves the strengthening of insulation in walls and/or the replacement of old windows, doors, and boilers.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the Korean government formalized an Energy and Welfare Statement; the Energy Act was legislated in 2006, and the government has operated the residential energy efficiency (retrofit) program for low-income households. The aims of this program are to improve the thermal performance and airtightness of households in fuel poverty, as well as to reduce heat loss, lower energy bills, and improve the thermal comfort and health problems of residents [15]. This program involves the strengthening of insulation in walls and/or the replacement of old windows, doors, and boilers.…”
Section: Introductionmentioning
confidence: 99%
“…Many residents of low-income households find it fairly or very difficult to pay bills to keep their homes warm or cool [28]. Therefore, the indoor temperature of low-income dwellings rarely satisfies the minimum temperature of 21 • C needed to avoid negative health impacts during winter [29,30]. Tadj et al studied 1082 low-income households in England to determine the heating characteristics of low-income households.…”
Section: Introductionmentioning
confidence: 99%
“…The average winter temperature of the living room and bedroom were 19 • C and 18 • C, respectively, both lower than 21 • C [31]. Song et al conducted field measurements in the winter season on 504 rooms and 330 households of low-income detached dwellings in Korea [30]. They found that about 95.2% of the main living rooms did not meet the 18 • C WHO threshold for adequate warmth.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation